In vivo biocompatibility and biodegradability of poly(lactic acid)/poly(ϵ-caprolactone) blend compatibilized with poly(ϵ-caprolactone-b-tetrahydrofuran) in Wistar rats - Conde, Gabriel [UNESP]; De Carvalho, Júlia Ribeiro Garcia [UNESP]; Dias, Paula Do Patrocínio; Moranza, Henriette Gellert [UNESP]; Montanhim, Gabriel Luiz [UNESP]; Ribeiro, Juliana De Oliveira [UNESP]; Chinelatto, Marcelo Aparecido; Moraes, Paola Castro [UNESP]; Taboga, Sebasti o Roberto [UNESP]; Bertolo, Paulo Henrique Leal [UNESP]; Gon alves Funnicelli, Michelli Inácio [UNESP]; Pinheiro, Daniel Guariz [UNESP]; et al. (IOP Publishing, 2021)
Poly(lactic acid) (PLA) and poly(ϵ-caprolactone) (PCL) are two important aliphatic esters known for their biodegradability and bioresorbability properties; the former is stiffer and brittle while the smaller modulus of the latter allows a suitable elongation. The new biomaterials being developed from the blend of these two polymers (PLA and PCL) is opportune due to the reducing interfacial tension between their immiscible phases. In a previous study, PLA/PCL immiscible blend when compatibilized with poly(ϵ-caprolactone-b-tetrahydrofuran) resulted in enhanced ductility and toughness no cytotoxic effect in vitro tests. There is little published data on the effect of poly(ϵ-caprolactone-b-tetrahydrofuran) on PLA and PCL biocompatibility and biodegradability in vivo tests. This study focuses on evaluating the behavioral response and polymer-tissue interaction of compatibilized PLA/PCL blend compared to neat PLA implanted via intraperitoneal (IP) and subcutaneous (SC) in male Wistar rats, distributed in four experimental groups: neat PLA, PLA/PCL blend, sham, and control at 2-, 8- and 24-weeks post-implantation (WPI). An open-field test was performed to appraise emotionality and spontaneous locomotor activity. Histopathological investigation using hematoxylin-eosin (H&E) and picrosirius-hematoxylin (PSH) was used to assess polymer-tissue interaction. Modifications in PLA and the PLA/PCL blend's surface morphology were determined by scanning electron microscopy (SEM). PLA group defecated more often than PLA/PCL rats 2 and 8 WPI. Conjunctive capsule development around implants, cell adhesion, angiogenesis, and giant cells of a foreign body to the biomaterial was observed in light microscopy. Both groups displayed a fibrous reaction along with collagen deposition around the biomaterials. In the SEM, the images showed a higher degradation rate for the PLA/PCL blend in both implantation routes. The polymers implanted via IP exhibited a higher degradation rate compared to SC. These findings emphasize the biocompatibility of the PLA/PCL blend compatibilized with poly(ϵ-caprolactone-b-tetrahydrofuran), making this biopolymer an acceptable alternative in a variety of biomedical applications.
Keywords: biodegradable; biodegradation; compatibilization; heatmap; open-field; PCL